2020
DOI: 10.21203/rs.3.rs-34197/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Restoring a butterfly hot spot by large ungulates refaunation: The case of the Milovice military training range, Czech Republic

Abstract: Background: Refaunation by large ungulates represents a cost-efficient approach to managing natural biotopes. We studied butterflies inhabiting grasslands of the former Milovice military training range in the Czech Republic, grazed since 2015 by a combination of Exmoor pony (“wild” horse), Tauros cattle (“aurochs”) and European wisent. Methods: We compared presence-absence patterns from two surveys preceding the refaunation, one immediately after military use termination (early 1990s), the other prior to the r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 59 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…A series of studies showed that hibernating larvae of high elevation Erebia species are less tolerant to cold (freeze‐avoidant) because they are adapted to survive the winter under a snow cover, while low elevation species exposed to unpredictable snow cover are freeze‐tolerant (Vrba et al ., 2012, 2017; Konvicka et al ., 2021). Erebia pandrose can be considered as a high elevation Erebia species since it tends to occur above 2000 m (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A series of studies showed that hibernating larvae of high elevation Erebia species are less tolerant to cold (freeze‐avoidant) because they are adapted to survive the winter under a snow cover, while low elevation species exposed to unpredictable snow cover are freeze‐tolerant (Vrba et al ., 2012, 2017; Konvicka et al ., 2021). Erebia pandrose can be considered as a high elevation Erebia species since it tends to occur above 2000 m (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Erebia populations living in high elevation areas are considered at risk because they rely on snow cover to resist the extremely cold mountain winter (Vrba et al, 2012(Vrba et al, , 2017Konvic ˇka et al, 2021). Thus, according to the typical orophilous and chionophilous character of Erebia, we selected the following variables: temperature annual range between the coldest and the warmest month, mean temperature of the coldest quarter, annual precipitation, and precipitation of the coldest quarter.…”
Section: Species Distribution Modellingmentioning
confidence: 99%
See 1 more Smart Citation